Diabetes during pregnancy and birthweight trends among Aboriginal and non-Aboriginal people in the Northern Territory of Australia over 30 years - Matthew J.L. Hare; Federica Barzi; Jacqueline A. Boyle; Steven Guthridge; Roland F. Dyck; Elizabeth L.M. Barr; Gurmeet Singh; Henrik Falhammar; Vanya Webster; Jonathan E. Shaw; Louise J. Maple-Brown (Elsevier, 2020)
Background: Early-life risk factors, including maternal hyperglycaemia and birthweight, are thought to contribute to the high burden of cardiometabolic disease experienced by Indigenous populations. We examined rates of pre-existing diabetes in pregnancy, gestational diabetes mellitus (GDM) and extremes of birthweight over three decades in the Northern Territory (NT) of Australia. Methods: We performed a retrospective cohort analysis of the NT Perinatal Data Collection from 1987 to 2016, including all births >20 weeks gestation, stratified by maternal Aboriginal identification. Key outcomes were annual rates of pre-existing diabetes, GDM, small-for-gestational-age, large-for-gestational-age, low birthweight (<2500 g), and high birthweight (>4000 g). Logistic regression was used to assess trends and interactions. Findings: 109 349 babies were born to 64 877 mothers, 36% of whom identified as Aboriginal ethnicity. Among Aboriginal women, rates of GDM and pre-existing diabetes, respectively, were 3 · 4% and 0 · 6% in 1987 and rose to 13% and 5 · 7% in 2016 (both trends p<0 · 001). Among non-Aboriginal women, rates of GDM increased from 1 · 9% in 1987 to 11% in 2016 (p<0 · 001), while pre-existing diabetes was uncommon (≤0 · 7% throughout). Rates of small-for-gestational-age decreased, while rates of large-for-gestational-age and high birthweight increased in both groups (all trends p<0 · 001). Multivariable modelling suggests that hyperglycaemia was largely responsible for the growing rate of large-for-gestational-age births among Aboriginal women. Interpretation: The burden of hyperglycaemia in pregnancy has grown substantially in the NT over three decades and is impacting birthweight trends. The prevalence of pre-gestational diabetes in Aboriginal women is among the highest in the world. Funding: Diabetes Australia Research Program.